The emperor's club - Canin, Ethan (Universal Pictures ; distributed by Viva Video, 2004)
When a new student starts in Professor Hundert's class, little does the professor know that this student will change his life forever. They start out butting heads and end up forming a friendship that will shake the controlled world of the professor. The lessons learned will last a lifetime.